RANCANG BANGUN PURWARUPA SISTEM KOMUNIKASI NIRKABEL VEHICLETO-INFRASTRUCTURE TERINTEGRASI GPS - Wira Yudha, I Made; Tirtha Santyani, Ni Nyoman; Indra ER, Ngurah; Sukadarmika, Gede; Purnama, Fajar (Jurnal SPEKTRUM; Vol 12 No 2 (2025): Jurnal SPEKTRUM, 2025)
Vehicle-to-Infrastructure (V2I) communication systems play a crucial role in the development of intelligent transportation systems (ITS), particularly for real-time traffic monitoring. This research focuses on the design and development of a V2I system prototype integrated with a Global Positioning System (GPS) for acquiring and communicating vehicle position and speed data. The prototype consists of an On-Board Unit (OBU) and a Roadside Unit (RSU) implemented using an ESP32 microcontroller, an NRF24L01 wireless communication module, and a Ublox Neo M8N GPS module. The system is designed to transmit vehicle data to the infrastructure to support traffic density monitoring. Functional testing was conducted under steady-state (stationary) and mobile-state (moving) conditions. Under steady-state conditions, the accuracy of position data transmitted by the OBU reached an average of 96.7% compared to validated reference coordinates. Under mobile-state conditions, the speed data from the OBU showed a good correlation with vehicle speedometer readings, with performance affected by GPS signal obstructions in urban environments. The research results demonstrate that this V2I system prototype can provide spatial and speed data with promising accuracy, potentially serving as a foundation for the development of intelligent traffic information systems.